Development of Dengue virus serotype-specific NS1 capture assays for the rapid and highly sensitive identification of the infecting serotype in human sera - Röltgen, Katharina; Ruggieri, Alessia; Jänisch, Thomas (The journal of immunology, 2018)
Dengue fever can be caused by one of four distinct dengue virus (DENV) serotypes that cocirculate in many parts of the world. Point of care serotype-specific nonstructural protein-1 (NS1) capture assays for the rapid serotyping of DENV in human sera would greatly support epidemiological surveillance and potentially also prognosis in individual patients. To ensure both serotype specificity and broad coverage of variants within serotypes, we have applied an innovative approach for the generation and selection of serotype-specific anti-NS1 mAbs. To elicit mAbs against conformational epitopes, NMRI mice were immunized with living HEK 293 transfectants expressing the native target Ags in multiple display on the cell surface. For each serotype, three different NS1 sequence variants were sequentially used for immunization of mice, hybridoma selection, and capture assay development, respectively. Selection of optimal combinations of capturing and detecting mAbs yielded highly sensitive and specific NS1 serotyping ELISAs (st-ELISAs) for the four serotypes. st-ELISA testing of 41 dengue patient sera showed a 100% concordance with the serotype determined by serotype-specific reverse transcriptase real-time quantitative PCR. The respective NS1 variants could be detected for ∼10 d after the onset of illness. Ab-dependent enhancement of DENV infections may be associated with a specific range of pre-existing anti-DENV serological Ab titers. Testing of patient sera with the developed st-ELISAs will not only be useful for epidemiological studies and surveillance, but it may also help to develop and validate assays that can distinguish protective versus enhancing Ab responses for risk assessment for the development of severe dengue disease in individual patients.
Gesehen am 10.04.2019